The non-designer's InDesign book essential design techniques for print projects - Williams, Robin 1953- (Peachpit Press, 2011)
Many designers and photographers own the entire suite of Adobe's creative products, but they manage to learn only one or two of the applications really well. If Adobe InDesign CS5.5 is the one app in the suite that makes you feel like you're entering a foreign country where you don't speak the language, Robin Williams provides the perfect travel guide and translator in this new edition to the best-selling Non-Designer's series. This fun, straight-forward, four-color book includes many individual exercises designed specifically to teach InDesign CS5.5 to beginners in such a way that you can jump in at any point to learn a specific tool or technique. Along the way, Robin offers design tips for making your work communicate appropriately and beautifully. Whether you need to create your own marketing materials for a small business or organization, or you want your student or business papers to be perceived as more professional, or you want to become more proficient with the design tools you already use, this book is the fastest and most efficient path to mastering basic tasks InDesign. In this non-designer's guide to InDesign CS5.5, you'll learn: How to create basic design projects, such as flyers, business cards, letterhead, ads, brochures, CD covers, and much more How to add images to your pages and crop, rotate, resize, and add effects to those images How to use InDesign's typographic tools to make your work look professional How to use style sheets so every job is easier to create and work with How to use tabs and indents with confidence and predictability How to create nice-looking tables to effectively organize data And, of course, the basics of working in InDesign with layers, panels, tools, etc.
Print version record
Keywords: Adobe InDesign (Electronic resource); Graphic design (Typography); Desktop publishing; Graphic arts; Arts graphiques; Éditique; graphic design; graphic arts; desktop publishing